PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN MENGGUNAKAN JASA ONLINE GO RIDE DI KOTA MAKASSAR - Nurlinda, Nurlinda; Jeheman, Yohanes (Jurnal Ekonomi Bisnis Kompetif, 2025)
This study aims to determine the Effect of Service Quality on Customer Satisfaction Using GoRide Online Services in Makassar City. The type of research used in this study is a quantitative method. Data collection techniques using questionnaires. Data analysis techniques used are simple linear analysis, coefficient of determination and partial test (t test). The results of the study show that based on the results of the t test obtained a value of 7.654 meaning that Service Quality has a positive and significant effect on GoRide Customer Satisfaction with a regression value of Y = 10.29 + 0.90X and the value of the correlation coefficient or relationship is 0.631. The output of the coefficient of determination (R Square) is 0.3969 which means that the influence of the independent variable Service Quality on the dependent variable Customer Satisfaction is 39.69%.